FACTORS THAT INFLUENCE THE INTEREST OF PATIENT REVISITS IN DHARMA YADNYA GENERAL HOSPITAL DENPASAR: FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP MINAT KUNJUNGAN ULANG PASIEN DI RUMAH SAKIT UMUM DHARMA YADNYA DENPASAR - Kadek Primadewi Primadewi; Zainal Firdaus Wardana (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2021)
This study analyzes the interest in revisits at the Dharma Yadnya General Hospital Denpasar with the aim of this study being to determine the factors that influence. This study uses the method of measure sampling adequacy (MSA). The results obtained were 62.056% of patients revisited Dharma Yadnya Hospital which was significantly influenced by 22 indicators with the highest loading factor being the cost variable